Prevalence of hypothyroidism in different occupational groups of Bangladeshi population (IMC Journal of Medical Science, 2020)
Background and aims: Hypothyroidism is a common global endocrine disorder. The magnitude of hypothyroidism at community level in Bangladesh is unknown except some clinic-based studies. The present study was undertaken to determine the prevalence of hypothyroidism in different occupational groups of Bangladeshi population and to assess the risks related to it.Study design: Three occupational groups (house-wives, college students, rickshaw-pullers) of native Bangladeshi population were purposively selected. Investigations included socio-demography, anthropometry, blood pressure and biochemistry [fasting blood glucose, lipids, thyroid stimulating hormone (TSH) and free thyroxin (FT4)]. Laboratory tests were done only on a randomized sample of participants.Results: Overall, 626 (M/F=123 / 503) participants with a mean age of 35.9 (34.75 – 37.02) years volunteered. The mean values of all participant for TSH and FT4 were 2.08 (95%CI: 1.72 – 2.45) μiu/ml and 13.04 (95CI:12.86 – 13.22) pmol/L respectively. The third percentile of TSH ranged from 0.42 to 0.46 μiu/ml and 97th percentile ranged from 5.16 to 5.24 μiu/ml. For FT4, the 3rd and the 97th percentile were 10.3 and 16.41 pmol/L, respectively. The prevalence of hypothyroidism in both sexes was 7.0% (M/F=4.1/8.3%). Occupational groups, sex and increasing age, obesity, blood pressure, and lipids showed no association with hypothyroidism. Hyperglycemia was proved to be a significant risk for hypothyroidism (prevalence in diabetic vs. non-diabetic was12.9% vs. 5.5%, p = 0.04; FBG was correlated with TSH, r = 0.138, p